Efficient Dye Contaminant Elimination and Simultaneous Electricity Production via a Carbon Quantum Dots/TiO2 Photocatalytic Fuel Cell - Zixuan Feng; Xuechen Li; Yueying Lv; Jie He (Crystals)
Conventional wastewater treatment methods do not fully utilize the energy in wastewater. This study uses a photocatalytic fuel cell (PFC) to remove dye impurities and generate electricity with that energy. Pt serves as the PFC’s cathode, while the carbon quantum dots (CQDs)/anatase TiO2 (A-TiO2) serve as its photoanode. The visible light absorption range of A-TiO2 can be increased by combining CQDs with A-TiO2. The composite of CQD and A-TiO2 broadens the absorption edge from 364 nm to 538 nm. TiO2’s different crystal structures and particle sizes impact the PFC’s power generation and dye contaminant removal. The 30 min photodegradation rate of methylene blue by the 20 nm A-TiO2 was 97.3%, higher than that of the 5 nm A-TiO2 (75%), 100 nm A-TiO2 (92.1%), and A-TiO2 (93%). The photocurrent density of the 20 nm A-TiO2 can reach 4.41 mA/cm2, exceeding that of R-TiO2 (0.64 mA/cm2), 5 nm A-TiO2 (1.97 mA/cm2), and 100 nm A-TiO2 (3.58 mA/cm2). The photodegradative and electrochemical test results show that the 20 nm A-TiO2 delivers a better degradation and electrochemical performance than other samples. When the 20 nm A-TiO2 was used in the PFC photoanode, the photocurrent density, open-circuit voltage, and maximum power density of the PFC were found to be 0.6 mA/cm2, 0.41 V, and 0.1 mW/cm2, respectively. The PFC prepared in this study shows a good level of performance compared to recent similar systems.